Obstructive Fibrinous Tracheal Pseudomembrane After Tracheal Intubation: A Case Report - Kang, Hyeon Hui (The Korean Academy of Medical Sciences, 2010)
Obstructive fibrinous tracheal pseudomembrane is a rare, but potentially fatal complication associated with endotracheal intubation. It has been known that the formation of tracheal pseudomembrane is related with intracuff pressure during endotracheal intubation or infectious cause. But in the patient described in this case, pseudomembrane formation in the trachea was associated with subglottic epithelial trauma or caustic injuries to the trachea caused by aspirated gastric contents during intubation rather than tracheal ischemia due to high cuff pressure. We report a patient with obstructive fibrinous tracheal pseudomembrane after endotracheal intubation who presented with dyspnea and stridor and was treated successfully with mechanical removal using rigid bronchoscopy.